A Retrospective Cohort Study of 45 Cases Treated With Surgery First Approach in Orthognathic Surgery and a Short Review. Issue 1 (March 2021) - Singh, Gaurav; Gurung, Utsav Singh; Mishra, Madan; Gaur, Amit
Study Design: Retrospective cohort study. Objective: The purpose of this study was to evaluate and share our experience with the surgery first approach (SFA) for correction of skeletal malocclusion. Methods: After consultation with the department of orthodontics, 45 patients with skeletal malocclusions suitable to undergo SFA were enrolled in this study (14 bimaxillary protrusion and 31 skeletal class III malocclusion). Le Fort I maxillary osteotomy, bilateral sagittal split ramus osteotomy, subapical osteotomy, and genioplasty were performed as required. After a healing period of 2 weeks, postoperative orthodontic treatment was started to achieve the final occlusion. Results: The mean duration of postoperative orthodontic treatment was 15.2 months, which is much shorter than the conventional orthodontic first approach (OFA) where presurgical orthodontic duration alone takes 12-24 months according to an individual. In the bimaxillary protrusion group, it was 18 months, which was significantly longer than for the other group ( P < .05). Conclusions: SFA offers an efficient alternative to conventional OFA with shorter total treatment duration, immediate marked improvement in facial profile, reduced biological costs, and similar operative stability. However, it comes at the cost of heightened challenges regarding case selection, accurate prediction, and surgical precision. With a joint venture between skilled and experienced surgeons and orthodontists, the outcome can be very promising.